Photoredox Properties of Homoleptic d6 Metal Complexes with the Electron‐Rich 4, 4′, 5, 5′‐Tetramethoxy‐2, 2′‐bipyridine Ligand. Issue 28 (4th September 2015) - Büldt, Laura A.; Prescimone, Alessandro; Neuburger, Markus; Wenger, Oliver S.
Abstract: A synthetic procedure leading to 4, 4′, 5, 5′‐tetramethoxy‐2, 2′‐bipyridine [(MeO)4 bpy] was developed, and the first three metal complexes with this ligand were synthesized. A few ligand precursor compounds, the final ligand, and its homoleptic iron(II) complex were characterized structurally by X‐ray diffraction. The combination of cyclic voltammetry, optical absorption, luminescence, and transient absorption spectroscopy provided detailed insight into the electronic structure of the entire series of homoleptic Fe II, Ru II, and Os II complexes. The ruthenium(II) complex is a more potent photoreductant than the [Ru(bpy)3 ] 2+ parent compound by approximately 0.4 V as confirmed by 3 MLCT excited‐state quenching experiments with a relatively mild oxidant, 1‐chloro‐4‐nitrobenzene. In the presence of methanesulfonic acid in CH3 CN, the photoexcited [Ru{(MeO)4 bpy}3 ] 2+ complex is able to undergo proton‐coupled electron transfer (PCET) with acetophenone to yield a ketyl radical. Chemically robust and potent photoreductants are of interest for the phototriggering of electron‐transfer reactions, for example, in photoredox catalysis, in dye‐sensitized solar cells, in fundamental studies of (proton‐coupled) electron transfer, or for the generation of solvated electrons. Abstract : A fourfold methoxy‐substituted 2, 2′‐bipyridine molecule was used as a ligand for homoleptic complexes with Fe II, Ru II, and Os II . The last two are strong electron donors in their long‐lived 3 MLCT excited states. Their ability to act as photoredox reagents in acidic media has been demonstrated with the example of acetophenone reduction by proton‐coupled electron transfer (PCET).